2004
DOI: 10.1097/00005176-200402000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Abdominal Pain: Symptom Subtypes Based on the Rome II Criteria for Pediatric Functional Gastrointestinal Disorders

Abstract: This study provides the first systematic empirical evidence that RAP, originally defined by Apley, includes children whose symptoms are consistent with the symptom criteria for several FGIDs defined by the Rome criteria. The pediatric Rome criteria may be useful in clinical research to (1) describe the symptom characteristics of research participants who meet Apley's broad criteria for RAP, and (2) select patients with particular symptom profiles for investigation of potential biologic and psychosocial mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
149
11
9

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(177 citation statements)
references
References 10 publications
8
149
11
9
Order By: Relevance
“…RAP is a symptom based pediatric classification, with at least three attacks of abdominal pain during three consecutive months that interferes with daily activity, which includes a higher percentage of patients who also meet IBS diagnostic criteria. 19,53 In a sample of 21 RAP cases, Dufton, et al 18 found no differences in cold-pressor tolerance or pain intensity, which is consistent with our findings and those of Williams et al cited above. In a small sample including 20 RAP cases, Zohsel, et al found no difference in heat pain threshold or pressure pain threshold between cases and controls.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…RAP is a symptom based pediatric classification, with at least three attacks of abdominal pain during three consecutive months that interferes with daily activity, which includes a higher percentage of patients who also meet IBS diagnostic criteria. 19,53 In a sample of 21 RAP cases, Dufton, et al 18 found no differences in cold-pressor tolerance or pain intensity, which is consistent with our findings and those of Williams et al cited above. In a small sample including 20 RAP cases, Zohsel, et al found no difference in heat pain threshold or pressure pain threshold between cases and controls.…”
Section: Discussionsupporting
confidence: 91%
“…Thus there is a risk of misclassifying organic diseases as IBS. Still, with the knowledge that most pediatric patients with abdominal pain have functional gastroenterological disorders, 10,30,53 and that IBS is the most common cause, 19 the risk of misclassification is most likely acceptably low if typical symptoms of IBS are present.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the predominant absence of organic diseases [1,54], the recurring occurrence of AP is mostly classified as a functional gastrointestinal disorder (FGID) [39]. Functional abdominal pain (FAP) and irritable bowel syndrome (IBS) are the most frequent FGIDs in childhood [10,23] and are characterized by recurrent or continuous AP for at least 2 months [39].…”
Section: Introductionmentioning
confidence: 99%
“…The aetiology, pathogenesis and prognosis of IBS are not well understood and there is no widely effective treatment [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%